THE OPPORTUNITY TO STUDY FOR STUDENTS IN THE REMOTE AREA OF SOUTHEAST ASIA AMID THE COVID-19 PANDEMICS. CASE STUDY: INTERNET CONNECTION AND ONLINE LEARNING IN MERAUKE PAPUA INDONESIA - Rudi Kogoya (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2022)
Abstract This paper will discuss about challenges for students in the remote area of Indonesia. Students in Merauke will be the case study of this paper. Millions of people have suffered from job loss and wage cuts due to the economic shocks caused by Covid-19 pandemic. Not just in the economic terms the pandemics also affected education especially for the student in the remote area. By April 2020, 188 countries around the world had imposed nationwide school closures, affecting more than 1.5 billion children and youth. As a result, many schools and institutions are now offering distance learning to their pupils. Unfortunately, not everyone has the luxury to opt for this. We can imagine how will it be for the student that live in the rural area in Merauke Papua the eastern part of Indonesia for instance. They have to denied the physical distancing policy issued by the government with attending to school amid the deadly pandemic, because they have no choice. There is no adequate internet connection. This paper will used qualitative research and interview method to collect the data and answer the research question How Students in Merauke Papua Deal With the Online Learning Program? It is a huge challenge for both the government to provide best services and student to adapt. Key Words: Covid-19, Indonesia, Internet, Students, Inequality.